Categorisation of cats: Managing boundary felids in Aotearoa New Zealand and Britain - Alexandra Palmer; Virginia Thomas (People and Nature, 2023)
Abstract Management of domestic and wild animals is an integral part of conservation and is often based on how an animal is categorised. For example, feral cats are often killed, while valued companion cats and native wildcats are protected. Drawing on qualitative research and using the concept of boundary‐work, this paper examines the complex categorisation and management of cats within conservation in Britain and Aotearoa, New Zealand (NZ). We examine how, both in theory and in practice, valued companion and wildcats are distinguished from unprotected feral cats, and in‐between categories of stray and hybrid cats. We demonstrate that stakeholders draw boundaries between cat categories differently. These differences in boundary‐drawing reflect the inherent blurriness of category boundaries, practical challenges and, importantly, differences in values, in particular whether priority is placed on the life of the cat or the cat's potential victim, particularly native or game birds. This can mean that laws outlining protections for specific categories of animals have limited effect if, in practice, those encountering cats draw boundaries differently. This paper also reports on important differences between the two case studies. In NZ, even cat advocates support the humane killing of unambiguously feral cats while this is less true in Britain. Furthermore, due to the nature of the contexts, conservationists in NZ are more inclined to assume that ambiguous cats are feral whereas conservationists in Britain are more inclined to assume that they are wildcats. This paper demonstrates that values not only shape people's perceptions and treatment of animals but also how they draw boundaries between them. This finding may have important implications for understanding other controversies in conservation and animal management. Read the free Plain Language Summary for this article on the Journal blog.